Pemahaman Guru Bk Terhadap Kode Etik Profesi Dalam Menjaga Kerahasiaan Data Konseling - Mawaddah Ramadhani; Asbi Asbi; Alman Faluthi; Jefano Albanua (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Data confidentiality is a fundamental principle in guidance and counseling services that determines the level of student trust in counselors. This study aims to analyze the level of Guidance and Counseling (BK) teachers' understanding of professional codes of ethics, specifically in maintaining the confidentiality of student counseling data in schools. The research method used is descriptive qualitative with a case study approach. Data collection was conducted through in-depth interviews, observation, and documentation studies of [Number] BK teachers in [Location/School Level]. Data analysis used interactive analysis techniques including data reduction, data display, and conclusion drawing. The results showed that, in general, BK teachers have a good understanding of confidentiality ethics regulations. However, in practical terms, BK teachers still face ethical dilemmas when confronted with pressure from school authorities (such as principals or homeroom teachers) who request the disclosure of student data for disciplinary purposes. This study concludes that cognitive understanding alone is insufficient; professional assertiveness and regular socialization regarding the boundaries of information disclosure in BK are required. The implications of this study emphasize the importance of strengthening professional advocacy and continuous ethical code development by professional organizations such as ABKIN..